Adaptation of the Digital Hoarding Questionnaire (DHQ) into an Indonesian Version - Dea Fenny Kirana Putri; Jihan Fadila Nawa; Aditya Briliant Ananta; Devi Lusiria (In Trend : International Journal of Trends in Global Psychological Science and Education, 2025)
This study aims to adapt the Digital Hoarding Questionnaire (DHQ) measurement tool into Indonesian and test its factor structure using the Exploratory Factor Analysis (EFA) approach. The background of this study is the increasing phenomenon of digital hoarding amidst the massive use of digital technology, especially among students and urban communities. Scale adaptation was carried out through several stages, starting from forward translation, back-translation, content validation by experts, and trials on 302 participants selected through purposive sampling techniques. The results of the reliability test showed that the Indonesian version of the DHQ had a Cronbach's Alpha value of 0.882, indicating high internal reliability. The KMO and Bartlett's Tests showed that the data was worthy of further analysis (KMO = 0.887; p <0.001). Exploratory factor analysis produced a one-factor structure with most items having a loading factor above 0.4. This scale is proven to be valid and reliable for use in the context of Indonesian culture. This study recommends the use of the Indonesian version of the DHQ in digital psychology research, as well as further testing through Confirmatory Factor Analysis (CFA) and application to a wider population.